Окиснене вугілля як сорбент для зм’якшення води - Войтко, І. І.; Денисович, В. О.; Кібальник, Т. В.; Сопрук, О. А.; Бондар, Р. В. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2021)
Sorption tests carried out oxidized nitric acid active carbon in H+- and Na+- form in relation to cations Mg2+ and Ca2+ and mixture thereof. Values obtained statistical volumetric capacity samples and mass loss them during processing nitric acid, that is oxidation state. Discovered correlation between these data and relevant sorption volume samples. Demonstrated a possible water softening oxidized coal subject to specific solution acidity.